2016
DOI: 10.1002/ajim.22666
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial employment characteristics and postpartum maternal mental health symptoms

Abstract: Our findings identified lack of workplace social support as a modifiable risk factor for postpartum anxiety. Future evaluations of workplace social support interventions may be explored to improve postpartum mental health symptoms. Am. J. Ind. Med. 60:109-120, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
1
6
0
2
Order By: Relevance
“…A study in Thai by Limlomwongse and Liabsuetrakulalso established that undesirable attitudes towards one's pregnancy double the risk of PPD [32]. Besides, a consistent finding was recorded with numerous earlier studies in Indonesia [30], Midwestern state [33], Turkey [31] and Ethiopia [20] in which unplanned pregnancy higher postnatal depression. Moreover, studies by Patel et al [62] concluded that a planned pregnancy was protective from developing depression in postnatal women which further strengthen the current result.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…A study in Thai by Limlomwongse and Liabsuetrakulalso established that undesirable attitudes towards one's pregnancy double the risk of PPD [32]. Besides, a consistent finding was recorded with numerous earlier studies in Indonesia [30], Midwestern state [33], Turkey [31] and Ethiopia [20] in which unplanned pregnancy higher postnatal depression. Moreover, studies by Patel et al [62] concluded that a planned pregnancy was protective from developing depression in postnatal women which further strengthen the current result.…”
Section: Discussionsupporting
confidence: 61%
“…Psychosocial and demographic variables cited as a contributory factor for postpartum depression includes poor social support [ 21 ], low education level, poverty [ 22 ], and childbirth without the presence of relatives [ 23 ], earlier history of depression [ 24 ], and poor woman autonomy [ 25 ]. Also, pregnancy, newborn and birth-related factors such as prime-parity [ 26 , 27 ], multiple children at home [ 28 ], multi-parity [ 29 ], unwanted or negative attitude toward pregnancy [ 20 , 30 33 ], premarital pregnancy [ 34 , 35 ], depression during pregnancy [ 29 , 36 ], miscarriage [ 37 ], and prenatal high anxiety [ 31 ] are some of the related factors for the high magnitude of postpartum depression. Moreover, husband and partner-related factors such as intimate partner violence [ 20 , 38 , 39 ], alcoholism in the husband [ 40 ], low husbands educational level [ 28 ], psychiatric problems in the husband [ 41 ], and husbands unemployment [ 30 , 42 ] were so far identified as associated factors.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with the latter, there is recent evidence that maternal work participation may have a positive influence on mental and somatic health (Klumb and Lampert, 2004; Buehler and O'Brien, 2011; Frech and Damaske, 2012; Cruise et al, 2018). Nevertheless, further results suggest a negative (in line with the scarcity hypothesis) or missing association between maternal work participation and the mother's mental and somatic health (Schwab-Reese et al, 2017; Liu et al, 2018). Consistent with findings on negative associations, women have been found to have a greater risk for suffering from work-privacy conflict than men probably due to multiple private and occupational burdens (Garthus-Niegel et al, 2016).…”
Section: Introductionmentioning
confidence: 92%
“…Even though every woman is potentially at risk of developing postpartum depressive symptoms, an early age of childbearing is more vulnerable to develop postpartum depression [7]; low education level, poverty [8], poor social support [9], and childbirth without the presence of relatives [10] were factors that increased the risks of depressive symptoms after delivery. Besides the above factors, previous history of depression [11], obstetric complication, miscarriage [12], parous women, an unplanned pregnancy [13], intimate partner violence [14], stressful life events [15], and poor woman autonomy [16] were factors of postpartum depressive symptoms. Postpartum depressive symptoms have physical and mental health consequences for mothers and their families.…”
Section: Introductionmentioning
confidence: 99%